Renalase Secreted by Human Kidney HEK293T Cells Lacks its N-Terminal Peptide: Implications for Putative Mechanisms of Renalase Action - Valerii Fedchenko; Arthur Kopylov; Nadezhda Kozlova; Olga Buneeva; Alexei Kaloshin; Victor Zgoda; Alexei Medvedev (Karger Publishers, 2016)
Background/Aims: Renalase is a recently discovered flavoprotein involved in regulation of blood pressure. Altered renalase levels have been found in blood of patients with end stage renal disease. The antihypertensive effect of circulating renalase is attributed to putative FAD-dependent monoamine oxidase activity demonstrated by some authors. Being synthesized as an intracellular flavoprotein renalase requires the presence of its N-terminal peptide for FAD accommodation. However, conventional routes of export of secretory proteins outside the cell usually include cleavage of their N-terminal peptide. The aim of this study was to investigate whether renalase is secreted by НЕK293T cells as a full length protein (via proposed nonconventional pathway) or its export is accompanied by the loss of its N-terminal peptide. Methods: We have expressed human recombinant renalase-1 in human kidney НЕK293T cells and analyzed this protein inside the cells and in the extracellular medium for the presence of the N-terminal peptide by using high resolution targeted MS/MS. Results: Intracellular renalase contained clearly detectable N-terminal peptide, which was absent in extracellular renalase. Conclusions: Lack of the N-terminal peptide, the structural precondition for FAD binding, suggests that extracellular (circulating) renalase acts in a FAD-independent manner and mechanisms of its action are not associated with FAD.